PENILAIAN PEMUSTAKA TERHADAP FUNGSI REKREASIONAL PERPUSTAKAAN KHUSUS DALAM MEMENUHI KEBUTUHAN INFORMASI - Ananda, Meydina Fauzia; S. Komarudin, Yooke Tjuparmah; Agustina, Susanti (Universitas Pendidikan Indonesia, 2017)
This research was based on the fact that the frequency of library visitation was still qualified as low due to the weary feeling of the staff to come to library during the break time. The general issue being examined in this study was whether or not the special library has fulfilled the recreationalfunction according to the user's need of information, along with the specific issues which covered the followings: 1) has the library of PT. Trisula Textile Industries implemented the recreationa function of the library?; 2) has the library of PT. Trisula Textile Industries fulfilled the information need of the PT Trisula Textile Industries' staff?. This research describes whether the library of PT. Trisula Textile Industries can be considered as fulfilling the recreational function of the library according to the user's need of information The population of this research was the staff of PT. Trisula Textile Industries, with the total of samples were 88 people which counted based on the Slovin formula. The sampling technique used was random sampling. The data collection was carried out by using the questionnaire which was based on Likert scale to gain certain answers. This research used a quantitative approach with a descriptive method. The result of this study indicates that the library of PT Trisula Textile Industries has implemented the recreation function of the library in fulfilling the user's need of information.